Lithium influences whole‐organism metabolic rate in Drosophila subobscura. Issue 1 (29th July 2020) - Kurbalija Novičić, Zorana; Bodén, Robert; Kozarski, Ksenija; Jelić, Mihailo; Jovanović, Vladimir M.; Cunningham, Janet L.
Abstract: Lithium is widely used to treat bipolar disorder. However, the efficacy and vulnerability as to its side effects are known to differ. Although the specific biochemical mechanism of action is still elusive, lithium may influence mitochondrial function, and consequently, metabolism. Lithium exposure in this study was conducted on a unique set of mito‐nuclear introgression lines of Drosophila subobscura to disentangle the independent effects of mitochondrial DNA (mtDNA) against a common nuclear DNA background. The study addressed three issues: (a) whether lithium has a dose‐dependent effect on whole‐organism metabolic rate, (b) whether mtDNA haplotypes show divergent metabolic efficiency measured by metabolic rate to lithium exposure and (c) whether lithium influences the whole‐organism metabolic rate across sexes. The results confirm that lithium influenced the whole‐organism metabolic rate, showing a subtle balance between efficacy and adverse effects within a narrow dose range. In addition, lithium exposure was found to influence metabolism differently based on mtDNA haplotypes and sex. This preliminary research may have a range of biological implications for the role of mitochondrial variability in psychiatric disease and treatment by contributing to the understanding and predicting of the lithium treatment response and risk for toxic side effects. Abstract : Metabolic parameters (O2 consmption and CO2 production) are influenced by lithium in dose‐dependent fashion showing a narrow therapeutic index with a subtle balance between low and high metabolic rate. We confirmed in vivo that treatment efficiency is dependent on mitochondrial genetic background and sex.